(untitled) (Reader's Digest Association, 2012)
The all-in-one trip planner and travel guide-now totally revised and updated-will steer you down the most scenic road every time. From Florida's Road to Flamingo to Hawaii's Oahu Coastal Loop . . . from British Columbia's Sea to Sky Highway to Cape Cod's Sandy Shores . . . each featured road trip is pictured in stunning full color and described in vivid text, keyed to an easy-to-follow newly revised map. Whether you choose a drive in a far corner of the continent or a back road in your own state, this book is your ticket to North America's most beautiful byways.
Keywords: Ô tô du lịch,Automobile travel; Sách hướng dẫn; Hoa Kỳ,United States